PENGARUH ADVOKASI HAK ASASI MANUSIA TERHADAP SIKAP PEDULI SOSIAL DAN KERJA SAMA ANAK DI DESA JEMUNDO - Utami, Eka Safitri; Srinarwati, Dwi Retnani (Academy of Education Journal, 2023)
Human rights of children need special attention, because various acts of violence against children are still found. When the child’s rigts have been fulfilled, then a child is obliged to become a citizen who has a good personality. This study aims to find out the effect of human rights advocacy on social care attitudes and child cooperation in Jemundo Village. Research using descriptive quantitative method. The research design uses quasi-experimental, experimental class (children participating in advocacy) and control class (children who did not participate in advocacy). The variables of this study are the independent variable advocacy for child human rights (X), the dependent variable social care attitude ( ) and cooperative attitude ( ). The research population is 300 children in Jemundo Village. Sampling using purposive sampling. The sample in this study were 30 experimental class and 30 control class of children 12-18 years old. The data collection technique uses a questionnaire instrument to determine differences in attitudes. Interviews and observations to gather data about advocacy processes, social care and cooperation. The subjects: children, parents, activists, and children's forums. Data analysis used descriptive analysis and the MANOVA test. The results showed: The significance value of the dependent variable is 0.00 < 0.05. Then the hypothesis Ho is rejected and Ha is accepted. This means that there is an influence of human right advocacy on social care attitudes and child cooperation in Jemundo Village.